(Post)archaiczność obrazu - Borowicz , Sebastian (Przestrzenie Teorii, 2020)
The proximity of the late archaic Greek philosophical breakthrough and postmodernity relies on the analogy of a media and intellectual revolution that takes place in both periods. Greek culture of the 6th and early 5th century BCE gradually moves from orality to literacy, from performativity and affection towards an intellectual view of the world and reflective being, from a world that is shared with non-human beings to the world of human monody. Modernity, however, seems to reverse these trends. Nevertheless, we do not go into the past but reach a higher level of archaicity. From this point of view, postmodernity becomes postarchaicity; this is a chance that in the moment of historical contiguity, vivisection of our culture will reveal still active common places, allowing us to explore images before the metaphysical era. The starting point of the analysis is the question “What is the image?” posed by Maurice Blanchot and his extremely insightful answer to this question.